Dynamics of active lamellae in cultured epithelial cells: effects of expression of exogenous N-ras oncogene. - Gloushankova, N A (1995)
We examined the functional consequences of cellular transformation of rat IAR-2 epithelial cells, by a mutant N-ras oncogene, on the dynamics of active lamellae, structures that play an important role in cell motility, adhesion, and surface-receptor capping. Lamellar activity was assessed by measuring the rate of outer-edge pseudopodial activity and by analyzing the motility of Con A-coated beads placed on lamellar surfaces with optical tweezers. Although transformation dramatically affected the shape and size of active cellular lamellae, there was little detectable effect on either pseudopodial activity or bead movement. To investigate the potential relationship between functional lamellar activity and the microtubule cytoskeleton, lamellar activity was examined in nontransformed and transformed cells treated with the microtubule-disrupting drug nocodazole. In the absence of microtubules, transformed cells were less polarized and possessed decreased rates of pseudopodial and bead motility. On the basis of these observations, it is suggested that ras-induced transformation of epithelial cells consists of two cytoskeletal modifications: overall diminished actin cytoskeletal dynamics in lamellae and reorganization of the microtubule cytoskeleton that directs pseudopodial activity to smaller polarized lamellae.